2020
DOI: 10.1002/admi.202000474
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographically Controlled Synthesis of SnSe Nanowires: Potential in Resistive Memory Devices

Abstract: Here we report the controlled growth of SnSe nanowires by a liquid injection chemical vapor deposition (CVD) method employing a distorted octahedral [SnCl4{ n BuSe(CH2)3Se n Bu}] single source diselenoether precursor. CVD with this single source precursor allows morphological and compositional control of the SnSex structures formed, including the transformation of SnSe2 nanoflakes into SnSe nanowires and again to SnSe nanoflakes with increasing growth temperature. Significantly, highly crystalline SnSe nanowir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 62 publications
1
17
1
Order By: Relevance
“…for multiple applications. The tin selenide based semiconductor materials have been synthesized using atomic layer deposition (ALD), 17 sputtering, 45 thermal evaporation, 46 hydrothermal, 47 spray pyrolysis, 48 chemical vapor deposition (CVD), 49 etc.…”
Section: Synthesis Of Snse and Snsementioning
confidence: 99%
“…for multiple applications. The tin selenide based semiconductor materials have been synthesized using atomic layer deposition (ALD), 17 sputtering, 45 thermal evaporation, 46 hydrothermal, 47 spray pyrolysis, 48 chemical vapor deposition (CVD), 49 etc.…”
Section: Synthesis Of Snse and Snsementioning
confidence: 99%
“…30,31 Although a huge range of different SnE and SnE 2 nanostructures have been synthesized in the solution phase, 32,33 very few 2D tin chalcogenide nanostructures have been prepared from SSPs. Different nanostructured SnE and SnE 2 materials have been synthesized using solution based SSP approaches, like SnSe nanorods, 28 SnSe nanowires, 34,35 SnSe needles, 36 SnS/Se nanoparticles 37 and few-layer SnSe/SnSe 2 nanosheets. 28,36 Despite these successes, the phase-controlled synthesis of 2D tin sulfide and selenide nanostructures remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Among selenium (Se)-based compound semiconductors, tin selenide (SnSe) (a band gap of approximately 1.0 eV) is a promising material because of its applications in thermoelectric devices, photovoltaic cells, field effect transistors (FETs), and resistive memory devices . SnSe is a layered semiconductor crystallized in an orthorhombic structure, which prefers a Se-rich structure at low temperatures (below 600 K) and a Se-deficient composition at high temperatures (above 600 K) .…”
Section: Introductionmentioning
confidence: 99%
“…Among selenium (Se)-based compound semiconductors, tin selenide (SnSe) (a band gap of approximately 1.0 eV) is a promising material because of its applications in thermoelectric devices, 1 photovoltaic cells, 2 field effect transistors (FETs), 3 and resistive memory devices. 4 SnSe is a layered semiconductor crystallized in an orthorhombic structure, 5 which prefers a Se-rich structure at low temperatures (below 600 K) and a Se-deficient composition at high temperatures (above 600 K). 6 Previous studies have suggested that the p-type conduction behavior of SnSe mainly originates from Sn vacancies ( V Sn ), and other highly localized vacancies merely act as immobile carriers that do not participate in the current transport.…”
Section: Introductionmentioning
confidence: 99%